'A strong woman's troubles': Victorina and the strong woman in Victorian Britain. Issue 3 (16th April 2021) - Heffernan, Conor
ABSTRACT: In 1893 Julia Veidlere, or 'Victorina', brought a court case against the London Pavilion Company. The previous year, Victorina was hired to perform a series of strength feats, including the lifting of a horse overhead. Owing to an unruly animal, Victorina failed to satisfy the Company's directors and was dismissed. In the wake of her dismissal Victorina brought a court case against the company. Ultimately losing the case, Victorina was soon declared bankrupt and fled to Europe. Examining Victorina's music hall career as a strongwoman, this article depicts Victorina as a prototype strength athlete. Victorina's fame, and disappearance, speak of the particularized environment female strongwomen found themselves in. Studying how Victorina built her 'brand' as a performer, as well as the structural barriers facing female strongwomen during this time, the article examines on a previously unstudied individual and an area in need of greater historical work in the British context.